Application of "Kato Nan Ampek" as an Alternative for Effective Counseling Communication - Asmita, Wenda; Silvianetri, Silvianetri; Hafiz, Luqman (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Application of "Kato Nan Ampek" as an Alternative to Effective Counseling Communication. The counselor deals with the clien twit havariety of issues related to thoughts, feelings, culture, disposition, customs andlanguage. Thecounselor must understand and adapttothe client's situation. This research discusses how the application of  KatoNan   Ampek   can be used as an alternative toeffective counseling communication. The research method usedis literature study, which is the analysis and synthesis of variousarticles    and    books. Research    shows    that counselorsmust first have the ability and personality to adaptto the client's situation. Counselor must consider, appreciate and respect the element soft he client's culture starting witht hecounselor's skill in sorting out the right words and expressionsfor   the   counselor.   Likewise,   counseling   communication with Kato Nan Ampek will be a communication full of ethic sandaesthetics. Keywords: Communication, counseling, effective.